NATIONAL AND CULTURAL SPECIFICITIES OF MANAGEMENT IN FRANCE - L. Efanova; V. Polyakova (Вестник университета)
National management models in each country have their own characteristics. When an international firm opens a new company abroad, one of its main tasks is to provide this company with managers, production workers. International managers need to take into account national differences between representatives of one or another cultural group in the performance of their work. International companies need to adapt and develop for each country training programs, hiring, firing employees. The purpose of the article is to study the national and cultural features of management on the example of France.